Outpatient transforaminal lumbar interbody fusion demonstrated favorable safety in comparison to the inpatient setting: analysis of 10,595 NSQIP patients and systematic review - Simon G. Ammanuel; Kaissa Sylla; Cuong P. Luu; Momin M. Mohis; Bradley Schmidt (World Neurosurgery: X)
Objective: To determine nationally how outpatient surgery affects transforaminal lumbar interbody fusion (TLIF) outcomes versus the inpatient setting. Methods: TLIF patients were identified from the National Surgical Quality Improvement database for the years 2015–2020 and stratified into inpatient and outpatient groups. Univariate and multivariate analyses, adjusting for differing patient characteristics, were performed to delineate outcome differences. A review of PubMed following PRISMA guidelines summarized prior level 3 evidence on how outpatient TLIF had affected outcomes. Results: Contrasting the characteristics of the 10,237 inpatient to 358 outpatient TLIF cases, the outpatient group fared younger (57.1 vs. 59.9 years old, p < 0.001) and lower in ASA >2 (42.2 % vs. 51.1 % p = 0.001). The outpatient group experienced shorter operations (183.86 vs. 214.29 min, p < 0.001), shorter stays (1.97 vs. 3.40 days, p < 0.001), and more home discharges (94.1 % vs. 87.1 %, p < 0.001). The outpatient group experienced fewer minor complications (4.7 % vs 10.7 %, p < 0.001), particularly perioperative blood transfusion (0.8 % vs 6.0 %, p < 0.001). Multivariate analysis showed outpatient group did not differ in major complications (OR 0.92, CI 0.45–1.88, p = 0.82) or readmissions (OR 1.06, CI 0.64–1.77, p = 0.82). A review of 7 smaller retrospective cohort studies revealed that complications rates (6 of 7 studies, p ≥ 0.05), the visual analog scale, and the Oswestry Disability Index (3 of 4 studies, p ≥ 0.05) did not differ between settings. Conclusions: TLIF can be performed safely in the outpatient setting with comparable outcomes to inpatient TLIF with prudent patient selection. It is also likely to have similar long-term functional outcomes, which therefore supports its expanded coverage under Medicare.